A Sulphide Paragenesis with Pyrrhotite and Marcasite in the Siderite-Cryolite Ore of Ivigtut, South Greenland. - Soen, Oen Ing; Pauly, Hans (Meddelelser om Grønland, 1967)
Sulphide nodules with pyrrhotite and marcasite occur enclosed in siderite masses in the siderite-cryolite ore of Ivigtut. From a detailed study of the structure of the nodules and of the textural relations of the minerals a sequence of five phases of mineral formation in the nodules is inferred. Approximate temperatures during the successive phases of mineral formation are deduced from mineralogical data, while variations in CO2- , S2- and O2-fugacities are inferred from the stability relations siderite-iron sulphides at various temperatures and CO2-pressures. It is concluded that the pyrrhotite-marcasite nodules and associated sulphides may have crystallized from fluids entrapped in siderite during crystallization of the siderite masses. The entrapped fluids were characterized by high CO2-pressures and relatively high S2-pressures and certain amounts of dissolved Pb, Cu, Zn and other metals. Crystallization occurred during cooling from over 500° C to approximately 200° C under conditions of decreasing CO2-, S2- and O2-pressures. The rate and amount of decrease of CO2-pressures, as compared with the decrease in temperature and S2-pressures, were significant in causing the stability fields of pyrite and pyrrhotite to encroache on that of siderite, so that iron sulphides could crystallize from the fluids. The development of concentric zones of pyrrhotite, chalcopyrite, sphalerite, pyrite, and galena is attributed to the control by fs2,-gradients around the nodules; the fs2,-isogrades shifted towards the core of the nodules in the course of time. Marcasite is believed to be a common hypogene mineral which is formed below 300° C in the course of cooling of Fe-sulphide-carbonate parageneses. If cooling is relatively slow, a decrease in CO2-pressures may cause the replacement of earlier carbonates by marcasite; if cooling is comparatively rapid replacement of pyrrhotite by marcasite, pyrite, and siderite may result.